Economia e sustentabilidade : um estudo sobre indicadores de desenvolvimento sustentável - Bourscheidt, Deise Maria (2011)
Economic development has historically been a central issue in Economics. Until the mid-1960s it referred only to increases in production, as a synonymous of economic growth, and consequently, increases in material wealth. In this context, macroeconomic indicators drawn to represent the economic reality had strictly aimed at quantifying the volume of goods and services produced. With the formulation of the concept of sustainable development, which adds to the economic dimension ,the social and the environmental ones, the fragility of traditional measurement methods (GDP) has being stressed. That began a process towards the building up of new methodologies and indicators, intended to measure sustainable development, nationally and internationally. These indicators are up until now quite incipient, and present advantages and limitations. Drawing upon this debate, in a context of economics and sustainability, this dissertation aims to study the sustainable development indicators, presenting national and international methodologies, using the bibliographic review method. The main finding of the present work is that, despite there have been advancements in the building up indicators both internationally and in Brazil, the measurement of sustainable development remains a major challenge for Economics as well as international agencies and government s nationals because it is not built up yet indicators and methods internationally accepted/validated and able to be adopted as comparison standards